Now, in order to solve for x, we need to multiply both sides of the equation by 3 to get rid of the fraction:
(1/3)x = -16
(1/3)x * 3 = -16 * 3
x = -48
1/3x - 4 = -12
First we subtract 4 from both sides.
4 - 4 and -12 - 4
leaving us with 1/3x = -16
Now what?
3 answers
Actually incorrect.
The answers provided are:
24
18
-18
-24
The answers provided are:
24
18
-18
-24
Apologies for the mistake. You are correct.
To solve the equation 1/3x - 4 = -12, we can follow these steps:
1. Add 4 to both sides of the equation to isolate the term with x:
1/3x - 4 + 4 = -12 + 4
1/3x = -8
2. To get rid of the fraction, multiply both sides by 3:
(1/3x) * 3 = -8 * 3
x = -24
So the correct answer is x = -24.
To solve the equation 1/3x - 4 = -12, we can follow these steps:
1. Add 4 to both sides of the equation to isolate the term with x:
1/3x - 4 + 4 = -12 + 4
1/3x = -8
2. To get rid of the fraction, multiply both sides by 3:
(1/3x) * 3 = -8 * 3
x = -24
So the correct answer is x = -24.